Analysis of psychological and sleep quality characteristics of young and adult para-athletes with cerebral palsy during competitive period - Muñoz-Hinrichsen, F.; Herrera-Miranda, F.; Riquelme, S.; Henríquez, M.; Álvarez-Ruf, J.; Cornejo, M. I.; Castelli Correia Campos, L. F. (Sports, 2025)
Emotional processes and sleep quality have become fundamental aspects of performance in Paralympic sports among elite and youth athletes. The objective of this study was to compare levels of depression, stress, anxiety, and sleep quality among youth and adult athletes with cerebral palsy (CP) belonging to the national CP Football team in Chile. A total of 10 adult and 12 youth national team athletes participated, completing the DASS-21, Pittsburgh Sleep Quality Index, and Epworth Sleepiness Scale questionnaires. The athletes were competing in their respective categories at the 2024 Parapan American Games. A cross-sectional design was used to compare the parameters of depression, stress, anxiety, and sleep quality of youth and adult male athletes with CP of a national team selected to compete in a regional event. Significant differences were found where young athletes had lower levels of depression (X2 = 4.77, p = 0.02, OR = 11.0) and anxiety (X2 = 6.71, p = 0.01, OR = 16.5). Similar differences could be observed in favor of young athletes in sleep latency (p = 0.04; d = 0.34), bedtime (p = 0.02; d = 0.20), total hours of sleep (p = 0.04; d = 0.10), subjective sleep quality (p = 0.002; d = 0.56), and objective sleep quality (p < 0.001; d = 0.65). This study suggests that adult para-athletes from a national CP Football team exhibit higher levels of depression and anxiety compared to their youth counterparts. Additionally, objective and subjective measures show that adults experience poorer sleep quality. These findings highlight the need for targeted interventions by psychological support teams, aiming to enhance athlete performance by promoting healthy habits that address these mental health challenges.